SYSTEMATIC RIVIEW OF PICTURES FOR ENGLISH LANGUAGE TEACHING - Dahlia Dahlia; Sri Handayani; Nafan Tarihoran (Adisam Publisher, 2025)
The integration of pictures in English Language Teaching (ELT) has been widely recognized as an effective tool to enhance students' comprehension, engagement, and motivation. This study aims to systematically review the existing literature on the use of pictures in ELT, analyzing their effectiveness, benefits, and challenges. A systematic review method was employed following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The study involved searching academic databases such as Scopus, PubMed, ScienceDirect, Mendeley, Taylor & Francis Online, Google Scholar, and Google Books, focusing on articles published between 2020 and 2025. The findings reveal that pictures significantly contribute to improving students' vocabulary acquisition, reading comprehension, and writing skills. Additionally, pictures help create an interactive and engaging learning environment. However, challenges such as selecting culturally appropriate images and ensuring proper implementation in diverse classroom settings remain. This study highlights the importance of carefully integrating pictures into ELT to maximize their pedagogical potential. Future research should explore innovative ways to optimize the use of pictures in digital learning platforms and assess their long-term impact on language proficiency.